Nilai Edukatif-Transformatif dalam Novel Epos Madame Kalinyamat Karya Zhaenal Fanani - Muryanti; Widayati, Mukti; Sudiyana, Benedictus (Kajian Linguistik dan Sastra, 2024)
Educative-transformative refers to the nature or characteristics of an educational process that is transformative. Transformative education focuses on profound changes in how a person thinks and acts, encouraging critical and reflective learning. One source of educative-transformative values can be found in the literary work, the novel *Madame Kalinyamat* by Zhaenal Fanani. Here, the source of educativetransformative values is literature, specifically a novel that addresses various life, economic, political, and socio-cultural issues arising from the competition for the throne in the Kingdom of Demak.This research aims to elucidate the transformative educational values found in Madame Kalinyamat and to describe its relevance as teaching material for the Merdeka Curriculum in Indonesian subject. Qualitative methods are used in this research. Data collection methods include note-taking, reading, and literature review. Dialectical analysis is part of the data analysis process. The research results identified several transformative educational values in Zhaenal Fanani's novel Madame Kalinyamat, including the religious value about a wife's loyalty to her husband based on devotion to God, moral and character values such as discipline, independence, firmness, and affection, as well as social values emphasizing healthy interpersonal relationships without demeaning others, exemplified by Queen Kalinyamat's relationship with her attendants. Additionally, the novel highlights gender equality between men and women in various aspects of life.